ANALISIS PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS TENAGA KERJA, TRANSMIGRASI DAN SOSIAL (DISNAKERTRANSOS )KEBUMEN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Parmin, Parmin (P4M STIE Putra Bangsa, 2016)
This study aims to determine the effect of work motivation and job satisfaction on the performance and work discipline on employee performance . The study population was all civil servants in the department of labor and social transmigration Kebumen district . This study used census method . our data obtained by giving questioner to all respondents who totaled 47 people . the technique used in this analysis is the analysis of lane ( path analysis) with SPSS 18 for windows . Statistical methods in this study include : validity, reliability , multicolinearity test , heterocedasticity test , normality test , multiple linear regression analysis , path analysis , t-test, F and coefficient of determination. The results showed that work motivation affect the work discipline , motivation affect the performance and job satisfaction affect the performance. labor discipline effect on performance and job satisfaction affect the working discipline with a value of rÃ‚Â² ( R square ) for structural equation I is 62.6 % means that job satisfaction and motivation influence the working discipline at 62.6 % . the remaining 37.4 % is influenced by factors beyond the research and structural equation II is 75.0 % meaning that work motivation , job satisfaction and work discipline affect the performance of the remaining 25.0 % 75.0 % is affected by factors beyond the research.